Evaluating Branding and Reputation Management Strategies of Kenya Meat Commission - Muchunku, Idah Gatwiri; Nicodemus, Okioma (Advances in Social Sciences Research Journal, 2022)
This paper evaluates the strategies applied in handling reputation and brand management of Kenya Meat Commission over the history of the corporate. A brief historical background of Kenya Meat Commission lays the foundation of the study by juxtaposing various brand and reputation management concepts and principles from desktop research. To achieve the study purpose, two specific objectives guided the researchers viz.: To analyse the branding and reputation management strategies through SWOT analysis of Kenya Meat Commission’s internal environment; and to assess the branding and reputation management strategies through PESTEL analysis of Kenya Meat Commission’s external environment. Desktop research methodology was used and empirical data from other regional countries specifically Botswana Meat Commission was used to comparatively guide critical assessment of Kenya Meat Commission. The study concluded that Kenya Meat Commission has failed over and over again due to poor branding and reputation management efforts as evidenced following the SWOT and PESTEL model analyses. The study recommends that Kenya Meat Commission should consider instituting a corporate communications department that will raise its branding and reputation management efforts and consequentially cause it to become a more profitable corporate in Kenya and beyond.